Visual thinking for design - Ware, Colin (Burlington, MA : Morgan Kaufmann, 2008)
Increasingly, designers need to present information in ways that aid their audiences thinking process. Fortunately, results from the relatively new science of human visual perception provide valuable guidance. In Visual Thinking for Design, Colin Ware takes what we now know about perception, cognition, and attention and transforms it into concrete advice that designers can directly apply. He demonstrates how designs can be considered as tools for cognition - extensions of the viewers brain in much the same way that a hammer is an extension of the users hand. Experienced professional designers and students alike will learn how to maximize the power of the information tools they design for the people who use them. Presents visual thinking as a complex process that can be supported in every stage using specific design techniques. Provides practical, task-oriented information for designers and software developers charged with design responsibilities. Includes hundreds of examples, many in the form of integrated text and full-color diagrams. Steeped in the principles of active vision, which views graphic designs as cognitive tools.
VISUAL QUERIES -- WHAT WE CAN EASILY SEE -- STRUCTURING TWO DIMENSIONAL SPACE -- COLOR -- GETTING THE INFORMATION: VISUAL SPACE AND TIME -- VISUAL OBJECTS, WORDS, AND MEANING -- VISUAL AND VERBAL NARRATIVE -- CREATIVE META SEEING -- THE DANCE OF MEANING.
Includes filmography and index.
Keywords: Visual perception; Art -- Philosophy; Visualization; Computer graphics; Thinking; Electronic books